Occurrence of a RAGE-Mediated Inflammatory Response in Human Fetal Membranes - Choltus, Héléna; Lavergne, Marilyne; Belville, Corinne; Gallot, Denis; Minet-Quinard, Régine; Durif, Julie; Blanchon, Loïc; Sapin, Vincent (Frontiers in Physiology, 2020)
Context: Sterile inflammation has been shown to play a key role in the rupture of the fetal membranes (FMs). Moreover, an early and exacerbated runaway inflammation can evolve into a preterm premature rupture of membranes and lead to potential preterm birth. In this context, we investigated the receptor for advanced glycation end-products (RAGE), an axis implied in physiological sterile inflammation, in conjunction with two major ligands: AGEs and High-Mobility Group Box 1 (HMGB1). Our first objective was to determine the spatiotemporal expression profiles of the different actors of the RAGE-signaling axis in human FMs including its intracellular adaptors Diaphanous-1 and Myd88. Our second goal was to evaluate the functionality of RAGE signaling in terms of FM inflammation. Methods: The presence of the actors (RAGE, HMGB1, Myd88, and Diaphanous-1) at the mRNA level was investigated by reverse transcription quantitative polymerase chain reaction (RT-qPCR) in the human amnion and choriodecidua at the three trimesters and at term. Measurements were conducted at two distinct zones: the zone of intact morphology (ZIM) and the zone of altered morphology (ZAM). Then, proteins were quantified using Western blot analysis and their localization was evaluated by immunofluorescence in term tissues. In addition, pro-inflammatory cytokine secretion was quantified using a Multiplex assay after the treatment of amnion and choriodecidua explants with two RAGE ligands (AGEs and HMGB1) in the absence or presence of a RAGE inhibitor (SAGEs). Results: The FMs expressed the RAGE-signaling actors throughout pregnancy. At term, RNA and protein overexpression of the RAGE, HMGB1, and Diaphanous-1 were found in the amnion when compared to the choriodecidua, and the RAGE was overexpressed in the ZAM when compared to the ZIM. The two RAGE ligands (AGEs and HMGB1) induced differential cytokine production (IL1 and TNF) in the amnion and choriodecidua. Conclusion: Considered together, these results indicate that RAGE signaling is present and functional in human FMs. Our work opens the way to a better understanding of FMs weakening dependent on a RAGE-based sterile inflammation.